Pengaruh Rasio Profitabilitas dan Leverage terhadap Harga Saham pada perusahaan BUMN Periode 2019-2023 - Asmarani, Putri Nuzula; Nurhasanah, Nunung; Nadeak, Banuara (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research was designed as exploratory quantitative research which aims to determine the effect of profitability and leverage ratios on stock prices. The data used comes from the financial reports of state-owned companies listed on the Indonesian Stock Exchange during the 2019-2023 period, with a sample size of 30 observations. Data analysis used multiple linear regression analysis techniques with the help of SPSS software. The research results show that simultaneously and partially there is a significant and positive influence between profitability and leverage ratios on share prices in state-owned companies on the Indonesia Stock Exchange for the 2019-2023 period.